The natural evolution of idiophatic epimacular membrane - Hejsek, Libor; Stepanov, Alexandr; Dohnalova, Alena; Rehakova, Tereza; Jiraskova, Nada (Biomedical papers, 2017)
Background and Aims: Epiretinal membrane (ERM) refers to a semi-translucent tissue layer found on the inner surface of the retina especially in older people. Surgical treatment remains controversial, optimal timing for such treatment is difficult to determine and data on the natural evolution of this disorder are limited. In this study we evaluated the natural course of idiopathic epimacular membrane in 49 patients (53 eyes). Materials and Methods: Retrospective evaluation of a group of 49 patients (53 eyes) with idiopathic epimacular membrane confirmed by biomicroscopy, photography and optical coherence tomography (OCT). Results: Patient age ranged from 51-85 years (median 72). The average follow-up was 21.3 months ( extpm 14). Between the initial and final best corrected visual acuity (BCVA) there was no statistically significant difference although there was a significant tendency to decrease in BCVA (Spearman P=0.05) during the follow-up. Initial BCVA correlated with initial central retinal thickness (CRT), final CRT, final volume, and age. The final BCVA significantly correlated with all parameters measured. Conclusion: BCVA during follow-up tended to decrease: difference of starting BCVA and final BCVA values depending on the time of monitoring is significant. This we attribute to a slow gradual progression of macular changes. But, initial and final BCVA measurements were not substantially different at the end. Thus, in the absence of any clear signs of ERM progression, we can safely postpone the decision whether to perform PPV.
Keywords: epimacular membrane; natural course; surgery; PPV